Penguatan SDM Petani dan Pengusaha Kopi untuk Peningkatan Kualitas Produk Kopi Di Desa Karang Sidemen Kabupaten Lombok Tengah - ZULFIKAR, WAHYUDI; Khalil, S.TP., M.Si., Fakhrul Irfan Khalil; Sella Antesty; Oki Saputra; Mi'raj Fuadi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Karang Sidemen Village is located in Nort Batukliang Subdistrict, Central Lombok Regency, West Nusa Tenggara, Indonesia. This village has promising potential for coffee bean production, which can significantly improve the welfare of the local community if managed properly. This potential includes various coffee varieties that can thrive in the nutrient-rich volcanic soil, offering unique flavors that can compete in both national and international coffee markets. However, this potential has not been fully optimized due to a lack of knowledge and education among farmers and the local community. Best practices in post-harvest handling of coffee beans, such as proper picking, correct processing, and optimal storage, are still not fully understood and implemented. Many farmers still use traditional methods that are less efficient, which can lead to a decrease in coffee bean quality and, ultimately, lower selling prices. To address these challenges, initiatives are needed to organize inclusive socialization and training activities that engage the entire community. Through socialization sessions, farmers and the local community will gain a deep understanding of the importance of applying proper picking methods and accurate coffee bean processing practices. Practical training sessions will enable farmers to enhance their skills, ensuring that each post-harvest stage is carried out with high efficiency and avoiding unwanted quality loss. By implementing the best practices obtained through these socialization and training efforts, Karang Sidemen Village is expected to overcome existing barriers. Through these efforts, it is hoped that coffee harvests can be optimized and the quality of local coffee products significantly improved. This will not only provide direct benefits to farmers but also increase the competitiveness of coffee products from this village in both local and international markets. With comprehensive education, it is expected that the local community can become agents of change to achieve higher quality standards, realizing the extraordinary potential of Karang Sidemen Village’s coffee plantations. Furthermore, collaboration with research institutions and universities can open opportunities for innovation in coffee cultivation and processing techniques. Research focusing on superior coffee varieties, environmentally friendly processing techniques, and effective marketing strategies can add value to coffee products from Karang Sidemen Village. Thus, this village will not only be known as a producer of high-quality coffee but also as a center of innovation and education in the coffee industry.